PENGARUH PENGEMBANGAN APLIKASI PEMETAAN VISUAL DAN PENCATATAN PELANGGAN TERHADAP PRODUKTIVITAS PENAGIHAN PADA PT.TELEKOMUNIKASI INDONESIA - Eny Rifani; Rumadi Hartawan; Rachmawaty Haroen (Jurnal Manajamen Informatika Jayakarta, 2021)
The writing of this paper aims to present visual mapping applications as an alternative to reduce billing productivity in PT. Indonesian Telecommunications. As for the background of this writing trying to find solutions to address constraints are not found that occur in the field. This is due to the increasing number of customers who use the internet in the region, especially Jakarta, in this case many customers who do not understand about the procedures of payment, due bills and internet disconnection, then there is a lot of arrears so that it becomes the duty of CTB (Caring Teritory Base) as the billing party, then it becomes a problem if the customer's address is incomplete, there is no information rt and rw , the name of the tower, as well as the floor of the building. It will be a concern for the company to reduce Revenue Loss due to unpaid bills, as well as not achieving the targets set by management to employees. The analysis method used by the author is Object Oriented Analysis. (OOA). OOA sees problems based on system user objects. With OOA can be created modeling system. The application of OOA in this study uses Unified Modelling Language (UML) diagram. The Unified Modelling Language (UML) diagrams that the authors use are the Use Case Diagram design of the Activity Diagram design, the Sequence Diagram design, and the Class Diagram design. Application development method or Software Development Life Cycle (SDLC) that the author applied is waterfall method. Waterfall method has a special feature that is the entire development process is carried out in sequence starting from the stage of concept planning, modeling, development, testing and maintenance of the system. This analysis found that the existence of Find&Go application can help in overcoming arrears problems that occur in the company.